HAK BERDAULAT, KEWAJIBAN YURISDIKSI DAN HAK-HAK LAIN DI ZONA EKONOMI EKSKLUSIF - Dwi Ramasari, Risti; Aprinisa, Aprinisa; Ainita, Okta (Faculty of Law-Universitas Bandar Lampung, 2020)
The international community has succeeded in compiling a law of the sea to regulate all forms of use of the sea as well as the benefits of the natural resources contained therein as outlined in the form of an agreement between States as known as United Nations Convention on the Law of the Sea 1982. The sea is divided into several parts / zones, namely the territorial sea, internal waters, contiguous zones, archipelagic waters, the exclusive economic zone and the high seas. The exclusive economic zone is an area beyond and adjacent to the territorial sea, subject to the specific legal regime established in this Part, under which the rights and jurisdiction of the coastal State and the rights and freedoms of other States are governed by the relevant provisions of this Convention. In the exclusive economic zone, coastal countries have sovereign rights for exploration and exploitation purposes, conservation and management of natural resources, both living and non-living, from the waters above the seabed and from the seabed and the land below and with respect to other activities for the purposes of exploration and economic exploitation of the zone, such as energy production from water, currents and wind; jurisdiction as defined in the relevant provisions of this Convention with respect to the creation and use of artificial islands, installations and structures, marine scientific research and the protection and preservation of the marine environment. Other rights and obligations as defined in this Convention Key words: Exclusive Economic Zone, Sovereign Rights, Jurisdictional Obligations